Highly frustrated liquid crystal phases in optically active dimers: synthesis and rich phase transitional behavior - Nayak, R. A.; Bhat, S. A.; Shanker, G.; Rao, D. S. S.; Yelamaggad, C. V. (New Journal of Chemistry, 2019)
Herein we report on the synthesis and characterization of four new series of optically active, nonsymmetric dimers in which cholesterol is covalently linked to a Schiff base core through an ω-oxyalkanoyl spacer. While the Schiff base core is substituted with n-butyloxy, n-hexyloxy, n-octyloxy, n-decyloxy and n-dodecyloxy tails, three even-parity spacers, namely, 4-oxybutanoyl, 6-oxyhexanoyl, 8-oxyoctanoyl, and an odd-parity spacer, namely, 5-oxypentanoyl, have been used to join the two cores. The experimental results show that the length and parity of the spacer and the length of the terminal tail play a vital role in deciding the phase sequences of the dimers. In general, the dimers possessing an even-parity spacer display enantiotropic LC phases such as chiral nematic (N*), twist grain boundary (TGB), smectic A (SmA), chiral smectic C (SmC*) and twist grain boundary phase with SmC* slabs (TGBC*). Some of these dimers display TGBC* over a wide temperature range. The dimers with an odd-parity (5-oxypentanoyl) spacer display, unlike their even-membered counterparts, blue phases (BPIII/II/I); besides, they stabilize N* and/or unknown smectic (SmX) phases. The circular dichroism (CD) measurements were carried out as a function of temperature on the planar texture formed by three even-membered dimers and an odd-membered dimer. The occurrence of a strong negative CD band in the N* phase of the even-membered dimers suggests a left-handed screw sense of the macroscopic helical structure, and the scenario is opposite in the case of an odd-membered dimer.

Conjunctive photoluminescence enhancement through plasmonic and photonic band-gap pathways in a chiral self-assembled system - Baral, Marlin; Krishna Prasad, S.; Bhat, Sachin A.; Nayak, Rashmi A.; Yelamaggad, C. V. (ChemPhotoChem, 2020)
We describe two parallel pathways for enhancing the intrinsic photoluminescence of an organic emitter dispersed in a liquid crystal (LC) medium. The pathways have independent origins: (i) Metal enhanced fluorescence (MEF) incorporating gold nanoparticles having an organic shell of pro-mesogenic cholesterol esters; and (ii) Matching the photonic band gap (PBG) due to the helical structure in a self-assembled chiral system with the excitation wavelength. This unprecedented combination of both pathways achieves a level of photoluminescence exceeding the sum of the contribution from the individual methods. This conjunctive protocol results in an overall enhancement by a factor of 37 between the emitter dispersed in a non-chiral LC and that appealing to both MEF and PBG pathways. Circular polarized luminescence measurements also show that this protocol helps in effective discrimination of chiral light achieving a large dissymmetry factor whose magnitude (+0.33) is comparable to the highest recorded to date. Electric field switching between two states is also shown to result in appreciable fluorescence modulation. Being generic in nature the protocol employed can be adapted to a variety of situations with the large magnitude as well the modulation level suitable for applications such as biosensors, various analyte detection, and other photonic devices.
Keywords: chirality; circularly polarized luminescence; liquid crystals; photonic band-gap; plasmonics